Visualization Analysis of Interrelationship between Temperature Profile and Water Distribution inside the PEFC. (3rd July 2019) - Shigemasa, Kaito; Sato, Hayate; Otsuki, Yota; Kurosu, Masato; Araki, Takuto
Abstract : Water management is very important for more spread of polymer electrolyte fuel cell (PEFC). Water distribution inside the PEFC must be kept proper and it is largely changed with the temperature profile change inside the PEFC. Therefore, the interrelationship between the temperature gradient and water distribution in the cathode gas diffusion layer (GDL) must be investigated in detail. In this report, X-ray computed tomography (CT) was used to visualize inside the cathode GDL. And thin film thermocouple (TFTC), which width is 30 µm and thick is 6 µm, has been fabricated by using micro electro mechanical system (MEMS) technology. With X-ray CT and TFTC, the interrelationship between temperature gradient in the direction of through-plane of the cathode GDL and water distribution inside the cathode GDL was investigated. From the results, we considered that temperature gradient may largely affect on water distribution and the PEFC performance.